Progressively greater biological carbon storage in the deep Atlantic during glacial inception - Monica Garity; David Lund; Hope Jerris; Jacquelyn McBride (Proceedings of the National Academy of Sciences, 2025)
Changes in oceanic circulation and carbon storage have been implicated as important drivers of atmospheric pCO 2 variability during the last glacial cycle (0 to 150 ka), though consensus on the mechanisms responsible remains elusive due to sparse marine carbonate chemistry reconstructions. Here, we present vertical profiles of carbonate ion concentration ([CO 3 2 − ]) from the Southwest Atlantic to investigate oceanic carbon sequestration during key intervals of atmospheric CO 2 change. During the first major decline in atmospheric CO 2 (115 to 109 ka), enhanced carbon storage occurred in the abyssal Atlantic (>3,500 m water depth). During the second decline in CO 2 (72 to 68 ka), enhanced carbon storage occurred throughout the deep Atlantic (>2,000 m water depth). Paired with δ 13 C and δ 18 O vertical profiles from the same locations, the [CO 3 2 − ] results suggest progressively greater sequestration of biological carbon occurred in the South Atlantic as the volume of Southern Source Water expanded during glacial inception. Shoaling of the carbonate ion saturation horizon during the second decline in pCO 2 resulted in seafloor calcium carbonate dissolution and enhanced alkalinity, likely contributing to further draw down of atmospheric CO 2 . We also document carbon release from the deep South Atlantic during glacial Terminations I and II when atmospheric CO 2 was rising. Overall, our results highlight the tight linkage between pCO 2 and deep Atlantic carbon storage over the last glacial cycle.